Ad-hoc networks and wireless : ADHOC-NOW 2014 International Workshops, ETSD, MARSS, MWaoN, SecAN, SSPA, and WiSARN, Benidorm, Spain, June 22--27, 2014, Revised Selected Papers /: ADHOC-NOW 2014 International Workshops, ETSD, MARSS, MWaoN, SecAN, SSPA, and WiSARN, Benidorm, Spain, June 22--27, 2014, Revised Selected Papers. (2015) - Unknown
No abstract available